2015
DOI: 10.1007/s00438-015-1061-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of AP2/ERF transcription factors in carrot (Daucus carota L.) reveals evolution and expression profiles under abiotic stress

Abstract: AP2/ERF is a large transcription factor family that regulates plant physiological processes, such as plant development and stress response. Carrot (Daucus carota L.) is an important economical crop with a genome size of 480 Mb; the draft genome sequencing of this crop has been completed by our group. However, little is known about the AP2/ERF factors in carrot. In this study, a total of 267 putative AP2/ERF factors were identified from the whole-genome sequence of carrot. These AP2/ERF proteins were phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…Cassava genome sequences suggested to contain a MYB domain were isolated and identified as candidate R2R3 MYB genes by using the Arabidopsis genome as a refs 3,37. R2R3 MYB genes were isolated from the cassava genome (JGI database, version 6.1) using annotations and BLAST analysis with an E-value cutoff set as 0.000013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassava genome sequences suggested to contain a MYB domain were isolated and identified as candidate R2R3 MYB genes by using the Arabidopsis genome as a refs 3,37. R2R3 MYB genes were isolated from the cassava genome (JGI database, version 6.1) using annotations and BLAST analysis with an E-value cutoff set as 0.000013.…”
Section: Methodsmentioning
confidence: 99%
“…R2R3 MYB genes were isolated from the cassava genome (JGI database, version 6.1) using annotations and BLAST analysis with an E-value cutoff set as 0.000013. The Arabidopsis R2R3 MYB genes were identified using the Arabidopsis Information Resource (TAIR)337. Each putative cassava R2R3 MYB gene was searched against the TAIR database by using BLAST to ensure that no additional related genes were selected337.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 AP2/ERFs (Apelata2/ Ethylene response factors) are one of the most important Tf families in plants which control different biotic and abiotic stress responsive pathways. 26,27 Based on DNA binding domain (DBD), AP2/ERFs are further divided into AP2, RAV (Related to Abscisic acid insensitive3/Viviparous1), DREB (subgroup A1-A6), ERF (subgroup B1-B6), and others. 28 The genes responsible for tobacco dehydration stress are expressed by the presence of DREBs.…”
Section: Post-waterlogging Stress In Plantsmentioning
confidence: 99%
“…In this study, ERF8 presented high expression during water deficit in A. hypogaea cultivars, suggesting its importance in the interaction with the DRE elements and in the tolerance and acclimatization processes of the plant (Dang et al, 2012). Li et al (2015) reported that AP2 and ERF proteins are part of important factors in plant transcription, regulating various development pathways and response to stress. The increase in the expression of genes of the ERF family in Arabidopsis and tobacco provides greater resistance to biotic and abiotic stresses (Park et al, 2001;Berrocal-Lobo et al, 2002;Pan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%